The mitochondrial Ras-related GTPase Miro: views from inside and outside the metazoan kingdom - Yamaoka, Shohei; Hara-Nishimura, Ikuko (Frontiers in Plant Science, 2014)
Miro GTPase, a member of the Ras superfamily, consists of two GTPase domains flanking a pair of EF hand motifs and a C-terminal transmembrane domain that anchors the protein to the mitochondrial outer membrane. Since the identification of Miro in humans, a series of studies in metazoans, including mammals and fruit flies, have shown that Miro plays a role in the calcium-dependent regulation of mitochondrial transport along microtubules. However, in non-metazoans, including yeasts, slime molds, and plants, Miro is primarily involved in the maintenance of mitochondrial morphology and homeostasis. Given the high level of conservation of Miro in eukaryotes and the variation in the molecular mechanisms of mitochondrial transport between eukaryotic lineages, Miro may have a common ancestral function in mitochondria, and its roles in the regulation of mitochondrial transport may have been acquired specifically by metazoans after the evolutionary divergence of eukaryotes.